Documentation for Athletic Training, Third Edition. - Konin, Jeff (SLACK, Incorporated, 2017)
Documentation for Athletic Training, Third Edition provides all the important and relevant information that a practicing athletic trainer needs to possess to provide accurate documentation. These topics include legal considerations, electronic medical records, and numerous tips for effective verbal and written communication styles.